Development and Characterization of Novel Hybrid Hydrogel Fibers. Issue 12 (7th July 2015) - Mirabedini, Azadeh; Foroughi, Javad; Romeo, Tony; Wallace, Gordon G.
Abstract: Biopolymeric continuous core‐sheath fibres, with an inner core of chitosan and alginate as the sheath, were fabricated for the first time without using a template. Hereby, the necessary conditions to achieve chitosan‐alginate core‐sheath fibre via a wet‐spinning process are presented. SEM micrographs show the cylinder‐shaped monofilament structure of the chitosan core surrounded by the alginate sheath. The coaxial fibres exhibit a 260% increase in ultimate stress and more than 300% enhancement in the Young's modulus compared to the alginate counterpart. Release profiles from the coaxial fibre were determined using a model component. The obtained results suggest that the fibres are likely to find applications as 3D tissue scaffolds capable of drug delivery. Abstract : A novel one‐step coaxial wet‐spinning process for the production of continuous core‐sheath biofibers, with an inner core of chitosan and alginate as the sheath, is reported. As‐prepared hydrogel fibers are characterized and optimized in terms of their morphological, mechanical, swelling, and release properties. The obtained results suggest that they are likely to find applications as tissue scaffolds capable of drug delivery.